2020
DOI: 10.1002/jcp.29730
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐related long noncoding RNA signature for predicting survival and immune checkpoint blockade in hepatocellular carcinoma

Abstract: Long noncoding RNAs (lncRNAs) show multiple functions, including immune response. Recently, the immune‐related lncRNAs have been reported in some cancers. We first investigated the immune‐related lncRNA signature as a potential target in hepatocellular carcinoma (HCC) survival. The training set (n = 368) and the independent external validation cohort (n = 115) were used. Immune genes and lncRNAs coexpression were constructed to identify immune‐related lncRNAs. Cox regression analyses were perfumed to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 57 publications
1
89
0
Order By: Relevance
“…The value of immune-related lncRNA has been shown in many cancers such as hepatocellular carcinoma (HCC), anaplastic glioma ( 37 ), glioblastoma multiforme ( 38 ), diffuse large B cell lymphoma ( 39 ), and breast cancer. In the research of HCC, Zhang et al identified that the immune-related lncRNA signature not only had a significant effect on survival prognosis but also had the possible role of evaluating the response to ICB (immune checkpoint blockade) immunotherapy ( 40 ). Shen et al discovered the 11-lncRNA signature of breast cancer and analyzed the correlation between the lncRNA prognostic signature and the infiltration of immune cell subtypes ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The value of immune-related lncRNA has been shown in many cancers such as hepatocellular carcinoma (HCC), anaplastic glioma ( 37 ), glioblastoma multiforme ( 38 ), diffuse large B cell lymphoma ( 39 ), and breast cancer. In the research of HCC, Zhang et al identified that the immune-related lncRNA signature not only had a significant effect on survival prognosis but also had the possible role of evaluating the response to ICB (immune checkpoint blockade) immunotherapy ( 40 ). Shen et al discovered the 11-lncRNA signature of breast cancer and analyzed the correlation between the lncRNA prognostic signature and the infiltration of immune cell subtypes ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the main treatments for HCC include radiofrequency ablation, surgical resection, immunotherapy, and liver implantation, among others. However, the clinical efficacy of treatments for specific patients is not satisfactory due to poor therapeutic targets, tumor immune escape and complications, leading to a low 5-year survival rate [7,14,28]. In past decades, studies focused on immunotherapy for various cancers have obtained meaningful breakthroughs, especially in melanoma, non-small cell lung cancer, and others.…”
Section: Discussionmentioning
confidence: 99%
“…Immune-related cells infiltration into the tumor microenvironment (TME) is a key reason leading to immune responses at primary and secondary tumor sites, which is tightly regulated by various mediators, such as chemokines. Several studies have indicated that a variety of different immune cells, including CD4 + and CD8 + T -cells, dendritic cells, and tumor-associated macrophages (TAMs), have been identified in different cancers, such as prostate cancer, HCC and others [13,14]. Chunying et al also demonstrated that CD4 + and CD8 + T-cells could be recruited into the TME after CXCR4 inhibition in sorafenib-treated HCC in a mouse model [15].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to a certain number of studies carried out to explore IRL signatures in several human malignancies [48][49][50][51][52][53][54], this was the rst study based on a comprehensive analysis that focused on IRL signature in CC. However, our study has some limitations.…”
Section: Discussionmentioning
confidence: 99%